2016
DOI: 10.1039/c5fo01222h
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of black, green and rooibos tea on osteoblast activity

Abstract: Globally, tea is the second most consumed beverage after water. Habitual tea intake has been associated with higher bone mineral density, particularly in postmenopausal women. This association may be due to its polyphenols and resulting protective antioxidant effects. While in vivo studies have shown improved bone outcomes with a consumption of individual purified tea polyphenols, it is unclear if a particular tea - due to its different profiles of polyphenols - is more beneficial than others. Therefore, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 33 publications
2
40
0
3
Order By: Relevance
“…29 Nash et al have reported an increase in mineralization, alkaline phosphatase activity and osteoblast differentiation markers in rooibos-tea treated osteoblast-like cells, in vitro, indicating possible beneficial effects of fermented rooibos tea at 1 and 10 µg ml -1 GAE of tea on bone health. 31 However little is known on the effects of rooibos on osteoclast formation and function. In this present study we made use of concentrations of 62.5-500 µg ml -1 (about 1-14 µg ml -1 GAE) of rooibos tea extracts, similar to the concentrations reported by Nash et al to promote osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…29 Nash et al have reported an increase in mineralization, alkaline phosphatase activity and osteoblast differentiation markers in rooibos-tea treated osteoblast-like cells, in vitro, indicating possible beneficial effects of fermented rooibos tea at 1 and 10 µg ml -1 GAE of tea on bone health. 31 However little is known on the effects of rooibos on osteoclast formation and function. In this present study we made use of concentrations of 62.5-500 µg ml -1 (about 1-14 µg ml -1 GAE) of rooibos tea extracts, similar to the concentrations reported by Nash et al to promote osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The results were different from previously reported studies showing that catechins comprise 30 to 36% of AGTE dry weight, whereas epigallocatechin-3-gallate (EGCG) constitutes up to 63% of the extract (Roomi et al, 2016). However, it is also reported that polyphenol content varies according to brewing time, type of tea, commercial brand and producing country (Nash and Ward, 2016) and this could explain the different polyphenolic content of AGTE in our study.…”
Section: Discussionmentioning
confidence: 58%
“…Previously reported In vitro finding supported that EGCG, the polyphenolic compound of green tea, has various downstream cytoprotective effects and can induce significant redox-sensitive antioxidant response (Nash and Ward, 2016). The protective activity is modulated with increase in cellular antioxidant mediators such as haeme oxygenase-1, glutathione, and antioxidant and DNA repair enzymes (Soares and Bach, 2009), which decrease basal DNA damage and ultimately cytoprotective prooxidant change.…”
Section: Discussionmentioning
confidence: 77%
“…Here, a similar concentration of polyphenols was used in supplements, which were shown to have reduced release rates during ALP-mediated mineralization. However, it is important to note there are also several studies where treatment with GTE has increased osteoblast differentiation, such as Ko et al [2011] who used rat mesenchymal stem cells, Saos-2 [Nash and Ward, 2016], and human osteoblast cells [Vester et al, 2014]. These cells showed increased levels of many differentiation indicators, including ALP activity, mineralization levels, and gene expression for proteins including sclerostin, osteopontin, and osteocalcin.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, other studies using osteoblast-like cells tended to use lower concentrations, compared to the doses of 64 and 128 µg/mL that we used. For example, rat mesenchymal stem cells [Ko et al, 2011], Saos-2 [Nash and Ward, 2016], and human osteoblast cells [Vester et al, 2014] all showed increased levels of cell differentiation and limited cytotoxicity when treated with GTE concentrations of around 10 µg/mL (a maximum of 50 and a minimum of 0.01 µg/mL). Another study, testing EGCG, demonstrated no toxic effect at 10 µg/mL [Lee et al, 2009b], and whilst higher concentrations are occasionally tested, exposure times are generally shorter.…”
Section: Discussionmentioning
confidence: 99%